Accuracy of mandibular proximal segment position using virtual surgical planning and custom osteosynthesis plates. Issue 2 (February 2022) - Harding, J.; Hartsfield, J.K.; Mian, A.S.; Allan, B.P.; Naoum, S.; Lee, R.J.H.; Goonewardene, M.S.
Abstract: The purpose of this study was to determine whether the use of custom osteosynthesis plates increased the accuracy of proximal segment position following bilateral sagittal split osteotomy in a cohort of 30 patients when compared to a control group of 25 patients who had surgery with conventional plates. Surgery was performed by a single surgeon between October 2015 and December 2017. Post-surgical cone beam computed tomography scans were segmented using Mimics Innovation Suite (Materialise NV), and surface-based superimposition was achieved using ProPlan CMF (Materialise NV). However, there was a tendency for the rotational error to be smaller in the custom group than in the control group. The root mean square error in both groups and for all variables fell within clinical parameters of 2 mm and 4°. In conclusion, the results of this study indicate that customized mandibular fixation plates do not necessarily improve the accuracy of the proximal segments post-surgically; however they may be of benefit in individual patients.